PERAN SISTEM INFORMASI MANAJEMEN DALAM MENINGKATKAN EFISIENSI OPERASIONAL DAN PENGAMBILAN KEPUTUSAN PADA GOJEK - Ahmad, Najwa Nazirah; P, Cindy Anastasya; R. M, Syafira Oktaviana; R, Annisa Suci; Z, Syakila Julia (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
Advances in information technology are driving more and more businesses to implement Management Information Systems (MIS). As a result, this research seeks to explore the role that MIS plays in facilitating Gojek's operations and decision-making. Using primary data collected from academic journals, this study uses a literature review and library-based research approach. By taking advantage of enhanced data integration, MIS can simplify procedures, minimize operational mistakes, and improve coordination between departments. Furthermore, by delivering timely, accurate, and pertinent data, MIS enhances the quality of managerial decision-making. As a result, MIS has made a major contribution to strengthening Gojek's strategic and operational benefits.Keywords : Decision-Making, Gojek, Management Information Systems, Operational Efficiency Improvement